Interspecific interaction involving the Ovambo Sparrowhawk Accipiter ovampensis in suburban Gauteng - Branfield, Andy (Biodiversity Observations, 2013)
I will document another method involving a stealthy sneak stoop from a low altitude flight hoping to catch potential prey by surprise as well as higher altitude interactions.